Relationship Between factors affecting the initiation of cigarette smoking among boys in a secondary school in Shah Alam - Abdul Kha’ar, Siti Natasha Amira; Zulkifli, Ahmad Fahim; Ahmad, Azmeer (Journal of Islamic, Social, Economics and Development, 2025)
Lifetime health behaviour usually forms during the teenage phase and marks a critical growth period. It is a crucial stage in developing healthy behavior such as cigarette smoking cigarettes. Good or bad habits that develop during youth are often carried over into adulthood. Therefore, this research aims to study the relationship between factors that influence the initiation of cigarette smoking and the smoking status among male students. The study was administered by an online survey using the Google Forms platform and was distributed to male students aged 16 and 17. Through purposive sampling, 182 out of 196 responded to the online survey. The majority of respondents in this study do not have family members and friends who smoke. In addition, most respondents do not like watching cigarette advertisements and, on average, will not smoke in the future. Next, this reveals that the smoking factor does not influence the respondent to become a smoker. At the same time, more than 80% of respondents believe that cigarette smoke is harmful to non-smokers. The results of the Pearson Correlation Coefficient Analysis show that the factors affecting the initiation of cigarette smoking and smoking status have a moderate relationship. Thus, the study results reveal there is no significant relationship between the factors influencing the initiation of cigarette smoking and the smoking status among boys aged 16 and 17. Therefore, there is a need for future studies to aim to cover all states in Malaysia to compile and obtain more extensive national data.